Metaphors of transformation of education and fitness for purpose: Towards a humanizing agenda - Rodny-Gumede, Y.; Chasi, C.T. (South African Journal of Higher Education, 2020)
Education is metaphorically tied to transformation. We apply this understanding to postcolonial and post apartheid South Africa, noting that, as far as we know, no one has commented on the curious ‘doubling down’ on the idea of change that is revealed by the conceptual contiguity evident in the construct ‘transformation of education’. While we do not conduct a metaphor analysis of transformation of education, we nevertheless draw on elements and concepts from such analysis to discern meanings from what we term ‘compound conceptual metaphors’ that frame discourses around transformation and education. We specifically discuss how the compound metaphor ‘transformation of education’ is linked to the metaphor of ‘fitness for purpose’. This directs us to new understandings of the work that the word ‘transformation’ does in talk of ‘transformation of education’ and in contestations over the meanings ascribed to ‘fitness for purposes’. This goes to show how such understandings can chart a way for a humanizing transformation agenda.